Sexual Assault Perpetrators' Justifications for Their Actions: Relationships to Rape Supportive Attitudes, Incident Characteristics, and Future Perpetration. (August 2015) - Wegner, Rhiana; Abbey, Antonia; Pierce, Jennifer; Pegram, Sheri E.; Woerner, Jacqueline
Perpetrators use rape supportive attitudes and sexual assault incident characteristics to justify forcing sex on their victims. Perpetrators who can justify their behaviors are at increased risk for future perpetration. This study examined the relationships between rape supportive attitudes, sexual assault incident characteristics, and the post-assault justifications of 183 men sampled from the community who self-reported committing at least one act of sexual aggression. Hierarchical multiple regression analyses indicated that rape supportive attitudes, expectations for having sex, misperceptions of sexual intent, victims' alcohol consumption, attempts to be alone with her, and the number of consensual sexual activities prior to the unwanted sex were significant predictors of perpetrators' post-assault use of justifications. Greater use of justifications was a significant predictor of sexual aggression over a 1-year follow-up interval. These findings demonstrate the need for further research exploring when and why perpetrators use post-assault justifications and whether they are amenable to change.